Lectins Labelled with Digoxin as a Novel Tool to Study Glycoconjugates - Jerka Dumić; Sandra Šupraha; Mirna Flögel; Gordan Lauc (Food Technology and Biotechnology, 2002)
In recent years it has become clear that carbohydrate portions of glycoconjugates are performing numerous vital physiological functions in higher organisms. However, since glycobiology is a relatively new science, and carbohydrate structures are highly complex, the continuous development of novel analytical techniques is necessary to support the process of understanding the intricate nature of glycoconjugate structure and function. The introduction of digoxin as a novel tag for labelling of lectins that are being used to analyse glycoconjugates in immunoassay-like techniques is described. Lectins labelled with digoxin have significant advantages over biotin- or digoxigenin-labelled lectins and will hopefully prove to be a useful addition to the repertoire of glycobiological tools.